International labour law under the Rome conventions - Deinert, Olaf (Baden-Baden, 2017)
"The International Labour Law demands against the background of increasing numbers of cases with international regard higher standards for legal advice: Which law is applicable, what is laid down by law, what is standardised in Europe? The handbook „International Labour Law under the Rome Conventions“ offers a full academic examination of the conflict-of-laws questions in Labour Law, as far as they are standardised in Europe (Rome I and for industrial action Rome II). It also deals with the unregulated or only partial regulated field of the law referring to the applicable employment law and answers detailed conflict-of-laws questions of the international Labour Law, especially: classification law governing formal validity connection factors for capacity and contractual capability connection factors for the employment contract special connecting rule for overriding mandatory provisions creation of the contract subject matter of the contract termination of the contract Post-termination effects of the employment contract industrial action".